Sed quis custodiet ipsos custodes? O potrzebie modyfikacji modelu kontroli decyzji Komisji Nadzoru Finansowego w prawie rynku kapitałowego - Jurczyński, Paweł (PRAWO i WIĘŹ, 2024)
This paper aims to analyze the role and competencies of the Polish Financial Supervision Authority in the supervision of the capital market, including the nature and type of sanctions applied by it, as well as to examine whether the model of judicial, administrative control of the Polish Financial Supervision Authority’s decisions regarding the application of sanctions adopted by the legislator guarantees the supervised entities an appropriate standard of protection of their rights. The conclusions from these analyses will then be used to formulate de lege ferenda postulates on the discussed topic.